Assessing mammal diversity in Xuan Lien Nature Reserve using molecular approaches - Huong Giang, Cao Thi; Minh, Le Duc; Thanh, Nguyen Van; Ha, Nguyen Manh; Hong Van, Nguyen Thi; Hai, Nguyen Dinh; Huong, Do Trong (Academia Journal of Biology, 2016)
Xuan Lien Nature Reserve in Thanh Hoa province has a high level of biodiversity, including such globally threatened mammals as the Clouded Leopard (Neofelis nebulosa), the Roosevelt’s Barking Deer (Muntiacus rooseveltorum), and the Northern White-cheeked Gibbon (Nomacus lecogenys). There were several field surveys conducted to determine the number of mammal species in the protected area. Nevertheless, for some species, convetional field techniques might not be able to survey them effectively due to their behavioral ecolgy, e.g., nocturnal mammals or arboreal primates. To investigate mammal diversity, with a focus on nocturnal mammals and arboreal primates in Xuan Lien, we used a molecular approach by sequencing two mitochondrial genes, cytochrome b and 16S rRNA, from hair and bone samples collected in the area. Our results confirmed records of threatened primates in Xuan Lien Nature Reserve, including three species of the genus Macaca, viz. the Stump-tailed Macaque (Macaca arctoides), the Assam Macaque (Macaca assamensis), and the Rhesus Macaque (Macaca mulatta), and the Phayre’s Leaf Monkey (Trachypithecus phayrei). Based on the study results, we also discovered the small-toothed palm civet (Arctogalidia trivirgata). This is the first record of the nocturnal mammal in Xuan Lien Nature Reserve.